Assessing the determinants of teachers’ job happiness in the private universities - Chen, Baohua; Ren, Guangxin; Liu, Yanjun (Frontiers in Psychology, 2022)
Teachers' job happiness in private universities is an important element for the healthy and orderly development of universities and an inevitable requirement for the construction of university faculty, and it has become a hot topic of research in the field of private higher education at present. However, there is still a lack of empirical studies on the factors influencing job happiness in private universities. This study constructs a theoretical model between professional identity, job competence, professional motivation, professional prospects, perceived fairness, job achievements and job happiness, and explores the specific drivers of teachers’ job happiness in private universities based on empirical research. The results of the data analysis showed that professional identity, job competence, professional prospects, perceived fairness, job achievements, and professional motivation all had significant effects on teachers' job happiness, and the effects were decreasing. This study examined the effects of job happiness in practice in private universities, which helped private universities to enhance teachers' professional identity, strengthen organizational support for teacher development, promote teachers' teaching ability, improve job competence, and build a developmental teacher evaluation mechanism.